Uji Kualitas DNA Darah Pada Kertas Whatman Yang Diisolasi Dengan CHELEX-100 Serta Variasi Waktu Penyimpanan - Rita Maliza; Lutfi Sukma Pratiwi; Dyah Aryani Perwitasari (Universitas Muhammadiyah Surabaya, 2021)
DNA extraction from dried blood spots was used for molecular analysis. Dried blood spots sample usually used FTA cards, but short-term use would come at a cost. This study aims to identify DNA extraction quality from dried blood spots in Whatman filter paper as an alternative storage sample. This study used 15 samples with three different storage time for 1, 3, and 7 days on 4°C. Dried blood samples were extracted using the Chelex-100 method, and qualitative were identified by electrophoresis. The DNA extraction was used as a template on PCR amplification of the gapdh gene. The result showed that DNA extraction showed band from 1, 3, and 7 days, and PCR amplification showed bands in 200 bp. In conclusions, DNA from dried blood samples was stored for 1, 3 and 7 days in Whatman filter paper were successfully extracted by the Chelex-100 method and can be used as a DNA template for PCR amplification.